Self‐Assembly Growth of Twisted Bilayer Graphene on Liquid Cu - Xue, Xudong; Zhou, Xiahong; Li, Dong; Liu, Mengya; Liu, Shan; Wang, Liping; Yu, Gui (Advanced materials interfaces, 2023)
Twisted bilayer graphene (tBLG) possesses various novel physical properties. Most of tBLG are fabricated by using artificial methods of stacking or folding single‐layer graphene. Chemical vapor deposition (CVD) has been verified that it holds great potential for preparation of large‐size high‐quality graphene. Therefore, it is significant for preparing tBLG in situ by using CVD technology. In this work, a novel approach is developed to directly prepare tBLGs on liquid Cu substrate. When the growth temperature exceeds a certain critical value, the state of aligned high‐quality single‐layer graphene domains grown on liquid Cu will be broken. Then, tBLG with twisted double‐layer regions is prepared in situ by rotating and intercalating between graphene domains. Experimental observations suggest that the liquid phase of Cu substrate and gas flow play a crucial role for the formation of tBLGs. These results demonstrate that the liquid Cu is an ideal potential substrate for preparing tBLGs with a full range of twisted angles and studying the formation mechanism of layer‐stacked materials. Twisted bilayer graphene (tBLG) is prepared by chemical vapor deposition on liquid Cu. When the growth temperature exceeds a certain critical value, the state of aligned high‐quality single‐layer graphene domains grown on liquid Cu is broken. Then, tBLG with twisted double‐layer regions is obtained in situ by rotating and intercalating between graphene domains.